A Novel Landfill Liner Material for Solidified Lake Sediment Based on Industrial By-Product and Construction Waste: Engineering Behavior and Cr(VI) Breakdown Characteristics - Wencheng Meng; Lin Guo; Jiayue Yuan; Shiyu Chen; Guanghua Cai; Haijun Lu (Buildings)
Engineering sludge, industrial waste, and construction waste are marked by high production volumes, substantial accumulation, and significant pollution. The resource utilization of these solid wastes is low, and the co-disposal of multiple solid wastes remains unfeasible. This study aimed to develop an effective impermeable liner material for landfills, utilizing industrial slag (e.g., granulated blast furnace slag, desulfurized gypsum, fly ash) and construction waste to consolidate lake sediment. To assess the engineering performance of the liner material based on solidified lake sediment presented in landfill leachate, macro-engineering characteristic parameters (unconfined compressive strength, hydraulic conductivity) were measured using unconfined compression and flexible wall penetration tests. Simultaneously, the mineral composition, functional groups, and microscopic morphology of the solidified lake sediment were analyzed using microscopic techniques (X-ray diffraction, Fourier transform infrared spectroscopy, scanning electron microscopy + energy dispersive spectroscopy). The corrosion mechanism of landfill leachate on the solidified sediment liner material was investigated. Additionally, the breakdown behavior of heavy metal Cr(VI) within the solidified sediment liner barrier was investigated via soil column model experiments. The dispersion coefficient was computed based on the migration data of Cr(VI). Simultaneously, the detection of Cr(VI) concentration in pore water indicated that the solidified sediment liner could effectively impede the breakdown process of Cr(VI). The dispersion coefficient of Cr(VI) in solidified sediments is 5.5 × 10−6 cm2/s–9.5 × 10−6 cm2/s, which is comparable to the dispersion coefficient of heavy metal ions in compacted clay. The unconfined compressive strength and hydraulic conductivity of the solidified sediment ranged from 4.90 to 5.93 MPa and 9.41 × 10−8 to 4.13 × 10−7 cm/s, respectively. This study proposes a novel approach for the co-disposal and resource utilization of various solid wastes, potentially providing an alternative to clay liner materials for landfills.